2005
DOI: 10.1182/blood-2004-09-3742
|View full text |Cite
|
Sign up to set email alerts
|

Genomic stability and functional activity may be lost in telomerase-transduced human CD8+ T lymphocytes

Abstract: To obtain the large amount of T cells required for adoptive immunotherapy in a clinical setting, T-cell lifespan extension by human telomerase reverse transcriptase (hTERT) transduction is of particular interest. However, constitutive expression of hTERT is associated with malignant transformation and thus warrants a detailed evaluation of the safety of hTERTtransduced T cells before clinical application. In view of this, we performed an extensive cytogenetic analysis of hTERTtransduced MART-1 (melanoma antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 43 publications
(168 reference statements)
0
20
0
Order By: Relevance
“…However, some studies have demonstrated chromosomal abnormalities in these hTERT-transduced T cells (332). Additionally, long-term hTERT-transduced T cells show accumulation of cyclin-dependent kinase inhibitors such as p21 and p16ink4a.…”
Section: Cd28mentioning
confidence: 99%
“…However, some studies have demonstrated chromosomal abnormalities in these hTERT-transduced T cells (332). Additionally, long-term hTERT-transduced T cells show accumulation of cyclin-dependent kinase inhibitors such as p21 and p16ink4a.…”
Section: Cd28mentioning
confidence: 99%
“…These include either BAC arrays from the Sanger Institute in Cambridge (UK), the University of California in San Francisco (UCSF, San Francisco, USA) and our Amsterdam laboratories (VUMC, The Netherlands); oligonucleotide CGH arrays from our laboratory in Amsterdam; and cDNA arrays from Stanford University ( Table 1). The new VUMC BAC array CGH and oligoarray CGH experiments were performed according to protocols previously described (Schreurs et al, 2005;van den IJssel et al, 2005) and data are available at Gene Expression Omnibus (GEO) http://www.ncbi.nlm.nih.gov/geo/ (Edgar et al, 2002), under Accession number GSE5051. The fallopian data set is available at http://cc.ucsf.edu/albertson/public/, all others are as stated in the references (Table 1).…”
Section: Data Collectionmentioning
confidence: 99%
“…TERT reprogrammed T cells mount effective immune responses following adoptive transfer into mice bearing tumor xenografts (118). However, although in vitro studies so far indicate that constitutive TERT expression achieves immortalization without malignant transformation, caution is urged with the clinical use of life span-extended human T cells because chromosomal instability, which is associated with tumor development, has been observed in human T cells constitutively expressing TERT (119,120).…”
Section: Figurementioning
confidence: 99%